Reducing antinutrients in faba bean (Vicia Faba) with lactic acid fermentation - Ikonen, Iida (My University, 2021)
Need for sustainable plant-based food is increasing as world’s population continues to grow and environmental emissions of food production need to be reduced. When considering opportunities to shift towards more plant-based diet, legumes, such as faba bean (Vicia Faba), are promising alternatives since they are rich in protein and contain also dietary fiber, vitamins, minerals and phytochemicals. However, pulses contain several antinutritional factors that may either decrease the nutritional value of the plant or cause flatus or bowel irritation among part of consumers, which limits the use of pulses for human consumption. Fermentation has been recently studied as an alternative to reduce antinutrients in pulses and improve their utilization. Aim of this study was to find suitable fermentation conditions to decrease the amounts of galacto-oligosaccharides, vicine, convicine and phytic acid in faba bean. Combination of faba bean and oat was fermented with two different lactic acid bacteria (LAB) consortia at 30 °C and 37 °C for 24, 48 or 72 hours. After the fermentation, oligosaccharides were analyzed by using high-performance anion exchange chromatography coupled with pulsed amperometric detection (HPAEC-PAD), vicines and convicines by using HPLC-DAD and phytic acid by using a commercial assay kit. In the best performing conditions, the total amount of galacto-oligosaccharides was completely degraded during fermentation. However, fermentation induced a formation of a new compound that was not identified in HPAEC. Vicine and convicine concentrations decreased by 99 % and 67-98 %, respectively, during fermentation depending on the used LAB consortium. Fermentation at studied conditions did not have remarkably effect on the amount of phytic acid in the samples. As sensory properties of the fermented samples were evaluated, selected LAB consortia seemed to affect the odor and taste.
Keywords: Faba bean, antinutrient, fermentation, lactic acid bacteria, vicine, convicine, phytic acid, galacto-oligosaccharide